Political Communication Channel Political Communication in The Development of Democracy on Legislative Election of DPR-RI in Bogor City (Jurnal Komunikasi Pembangunan, 2020)
In developing democracy, political communication is needed through various existing communication channels, especially in elections where the public needs a lot of political information needed as material in determining political decisions. This study aims to determine the effect of mass political communication channels, interpersonal communication channels and organizational communication channels on the decision to vote for parties in the DPR RI legislative elections in Bogor City in 2019. The research uses quantitative methods with a survey design with a sample of 240 voters in Bogor City. Determination of the sample using multistage random sampling techniques and data obtained using multinominal logistic regression analysis. The results showed that open campaigns, social media, blusukan, volunteers and religious leaders influenced the decision significantly to vote the party. Meanwhile, television media, billboards / posters, newspapers and face-to-face dialogues proved to have no effect in the decision to vote.